Vertical Hydraulic Conductivity of Unsaturated Zone by Infiltrometer Analysis of Shallow Groundwater Regime (KUISG) (Journal of University of Babylon for Engineering Sciences, 2018)
A hydrogeologic model was developed and carried out in Taleaa district of 67km2 . The study adopted a determination of KUISG depends upon the double rings infiltrometer model. The tests were carried out in a part of Mesopotamian  Zone which is covered with quaternary deposits  . In general the groundwater levels are about one meter below ground surface.  Theoretically, the inclination angle of the saturated water phase plays an important role in the determination of KUISG. The experimental results prove that the angle of inclination of the saturated phase is identical to the angle of internal friction of the soil. This conclusion is supported by the comparison of the results that obtained from falling head test and infiltrometer measurements for estimating the hydraulic conductivitiy values for ten locations within the study area. The determination of vertical hydraulic conductivity by current infiltrometer model is constrained to only the shallow groundwater regime.7